Analisis Potensi Bahan Pakan Guna Mendukung Industri Pakan Sapi di Provinsi Nusa Tenggara Barat - Fitratunnisa fitratunnisa; Dahlanuddin Dahlanuddin; Hermansyah Hermansyah (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2022)
The purpose of this study was to determine the potential development of feed ingredients and the carrying capacity of land to support the cattle feed industry, what feeds can be applied in West Nusa Tenggara Province based on the potential of cattle feed ingredients and to determine the relationship between the area, type and breadth of feed sources, the number and area of grazing fields, population, amount of feed, types of feed sources, capacity, livestock population and livestock institutions in Sumbawa and East Lombok Regencies. Determination of the research location is done purposively. This study uses a survey approach combined with secondary data analysis. The results of the study show that the cattle feed ingredients industry in the two regions is quite potential to be developed. In addition, the available feed factor is relatively adequate, supported by the community's experience in raising livestock, making this business prospective to be developed. Institutionally, as many as 30 livestock farmer groups in Sumbawa Regency and East Lombok Regency with land ownership of 218 hectares in both regencies have the potential to support the development of the cattle feed industry in these two areas.